2008
DOI: 10.2217/17435889.3.5.647
|View full text |Cite
|
Sign up to set email alerts
|

LANTCET: Elimination of Solid Tumor Cells with Photothermal Bubbles Generated Around Clusters of Gold Nanoparticles

Abstract: Single 10 ns laser pulses generated intracellular photothermal microbubbles at a near-infrared and visible wavelengths. The cells with the clusters yielded an almost 100-fold decrease in the laser fluence threshold for bubble generation and cell damage relative to that for the cells without clusters. Cell damage had a mechanical origin and single cell selectivity. Three LANTCET processes (cell detection, damage and optical guidance) were realized as a microsecond sequence and with the one device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 96 publications
6
90
0
Order By: Relevance
“…PTT using spherical gold nanoparticles [103][104][105][106][107][108][109][110][111][112][113][114][115][116] can be achieved with pulsed or cw visible lasers due to the SPR absorption in the visible region and thus such treatment is suitable for shallow cancer (e.g. skin cancer).…”
Section: Photothermal Therapy (Ptt)mentioning
confidence: 99%
See 1 more Smart Citation
“…PTT using spherical gold nanoparticles [103][104][105][106][107][108][109][110][111][112][113][114][115][116] can be achieved with pulsed or cw visible lasers due to the SPR absorption in the visible region and thus such treatment is suitable for shallow cancer (e.g. skin cancer).…”
Section: Photothermal Therapy (Ptt)mentioning
confidence: 99%
“…Later they demonstrated the technique in vitro on the treatment of some other type of cancer cells such as cervical and breast cancer using the laser induced-bubbles under nanosecond laser pulses [105][106][107]. Recent work has demonstrated the treatment modality for in vivo tumor ablation in a rat [115]. Intracelullar bubble formation results in individual tumor cell damage.…”
Section: Photothermal Therapy (Ptt)mentioning
confidence: 99%
“…132,133 Recently, antibody-targeted gold nanospheres were developed to specifically target the EGFR on squalors carcinoma cells, and following stimulation by single 10 ns laser pulses at visible wavelengths, the resultant AuNPs generated intracellular photothermal micro bubbles and induced PTT for tumor inhibition in a subcutaneous cancer model. 134 To treat tumors under the skin, NIR-active PTT is favorable as the light can penetrate more deeply due to the minimal absorption of the hemoglobin and water in tissues in this spectral region. Therefore, it is important to tune the SPR absorption of AuNPs to the NIR region by means of altering the shape, morphology, and structure, as described in the "Optical characteristics of AuNPs" section.…”
Section: Aunps For Cancer Phototherapy Pttmentioning
confidence: 99%
“…5 With a localized near-infrared (NIR) laser exposure, the photothermal conversion (PTC) agents can convert optical energy into heat to kill cancer cells locally, without the risk of destroying healthy tissues. 6,7 Recently, the PTC effects of many materials have been revealed, such as gold-based nanostructures, [8][9][10][11][12][13] carbon nanotubes, 14 graphene, 15,16 CuS nanocrystals, 17 polypyrrole, 18 and porphysome, 19 high concentration for the PTT of cancer. 21 Zhang group and our group further demonstrated that Fe 3 O 4 superstructures exhibited better photothermal effect with a significantly increased NIR absorption than individual Fe 3 O 4 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%